2013
DOI: 10.2146/ajhp130088
|View full text |Cite
|
Sign up to set email alerts
|

Cost comparison of drug–drug and drug–condition interactions in patients with painful diabetic peripheral neuropathy treated with pregabalin versus duloxetine

Abstract: Among patients with painful DPN treated with either pregabalin or duloxetine, the frequency of potential duloxetine DDIs and DCIs was substantially higher than that of pregabalin. Potential DDIs and DCIs were associated with significantly increased health care costs in duloxetine users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“… 37 This same study found that potential DDI exposed patients versus nonexposed patients experienced significantly more office visits (19.10 vs 18.29; P <0.01), outpatient visits (6.71 vs 6.39; P <0.01), emergency department visits (0.46 vs 0.43; P <0.01), and inpatient hospitalizations (0.13 vs 0.12; P <0.01). 36 While these overpowered statistically significant differences may be difficult to interpret in terms of absolute clinical relevance, the increase in health care utilization in the presence of potential DDI exposure is directionally consistent. The only significant, albeit directionally consistent, finding in the present study regarding health care utilization was an increase in all-cause, nonphysical therapy outpatient visits for duloxetine members exposed to a potential DDI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 37 This same study found that potential DDI exposed patients versus nonexposed patients experienced significantly more office visits (19.10 vs 18.29; P <0.01), outpatient visits (6.71 vs 6.39; P <0.01), emergency department visits (0.46 vs 0.43; P <0.01), and inpatient hospitalizations (0.13 vs 0.12; P <0.01). 36 While these overpowered statistically significant differences may be difficult to interpret in terms of absolute clinical relevance, the increase in health care utilization in the presence of potential DDI exposure is directionally consistent. The only significant, albeit directionally consistent, finding in the present study regarding health care utilization was an increase in all-cause, nonphysical therapy outpatient visits for duloxetine members exposed to a potential DDI.…”
Section: Discussionmentioning
confidence: 99%
“… 34 , 35 A recent study, while in a predominantly commercially insured diabetic peripheral neuropathy (DPN) population, substantiates the findings of the present study. Specifically, Johnston et al 36 found the frequency of potential contraindicated, major, and moderate DDIs in DPN patients newly initiated on duloxetine to be 3.9%, 36.9%, and 33.8%, respectively. Conversely, no DPN patients newly initiated on pregabalin encountered a potential DDI of any severity.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, pregabalin and duloxetine are the first-line therapies for pDPN and have been approved by the US Food and Drug Administration [11,12]. However, pDPN patients are often subject to polypharmacy and comorbidities related to hyperglycemia and other microvascular and macrovascular complications, increasing the risk of drug-drug and drug-condition interactions [13].…”
Section: Introductionmentioning
confidence: 99%
“…As such, anticipating and controlling DDIs in patients with pDPN presents a significant challenge to providers, particularly in an older population. The consequences of these drug interactions have the potential to impact the quality of life of the patient, as well as increase the cost of the disease [ 9 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…While some studies have examined aspects of treatment outcomes such as healthcare utilization and economic comparisons between pregabalin and duloxetine (where the costs were found to be comparable between the two drugs), few studies have documented the costs incurred from DDIs related to treatment of patients with pDPN [ 29 , 34 - 36 ]. Recently, Johnston et al [ 34 ] examined the frequency and financial impact of DDIs and drug-condition interactions (DCIs) in predominantly commercially-insured pDPN patients prescribed pregabalin or duloxetine and found patients taking duloxetine had a substantially higher potential for DDIs and DCIs than patients taking pregabalin. Furthermore, the costs associated with potential DDIs and DCIs in patients taking duloxetine were found to be significantly increased.…”
Section: Introductionmentioning
confidence: 99%